Seismicity and shallow slab geometry in the central Vanuatu subduction zone. Issue 8 (13th August 2015) - Baillard, Christian; Crawford, Wayne C.; Ballu, Valérie; Régnier, Marc; Pelletier, Bernard; Garaebiti, Esline
Abstract The Vanuatu arc in the southwest Pacific Ocean is one of the world's most seismically active regions, with almost 39 magnitude 7+ earthquakes in the past 43 years. Convergence rates are around 90–120 mm/yr along most of the arc, but drop to 25–43 mm/yr in the central section, probably due to the subduction of the d'Entrecasteaux ridge. We characterize the slab geometry and tectonic state in this central section by analyzing data from a 10 month deployment of 30 seismometers over this section. We located more than 30, 000 events (all less than magnitude 5.5), constructed an improved 1‐D velocity model, calculated focal mechanisms and cluster geometries, and determined the 3‐D geometry of the interplate seismogenic zone. The seismogenic zone has a shallow bulge in front of the d'Entrecasteaux ridge, which could be explained by the ridge's buoyancy contributing to the uplift of the fore‐arc islands. The seismogenic zone extends to ~45 km depth, significantly below the 26–27 km depth of the fore‐arc Moho, indicating that the upper mantle wedge is not significantly serpentinized, which is consistent with the relatively high thermal parameter of the subducting plate. The maximum width of the seismogenic zone is 80 km, indicating an upper earthquake magnitude limit of Mw 7.85 ± 0.4, assuming standard rupture zone aspect ratios. The data also reveal a double seismic zone, 20 to 30 km below the seismogenic zone, which is presumably caused by flexure of the downgoing plate.